Syagrus romanzoffiana: Queen Palm - Timothy K. Broschat (EDIS)
The queen palm is a popular feather-leaved palm with graceful arching leaves. It is one of the hardiest of the tropical-looking palms, being suitable for planting in USDA plant hardiness zone 9B (>25°F). Queen palms are considered to be moderately tolerant of salt spray. This 5-page fact sheet was written by Timothy K. Broschat, and published by the UF Department of Environmental Horticulture, October 2013. http://edis.ifas.ufl.edu/st609